A stitched structure battery based on capillary compensation wetting and anti-bridging and a preparation method thereof
Patent Information
- Application Number
- CN202611146638.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]鉴于上述现有技术的不足,本发明的目的在于提供一种基于毛细补偿浸润与防架桥的缝合结构电池及其制备方法,旨在解决现有缝合结构电池在缝合后电解质浸润阶段容易出现隔膜压实、线束含气、干斑、架桥、电解质池和短路风险的问题
[0015]有益效果:本发明提供一种基于毛细补偿浸润与防架桥的缝合结构电池及其制备方法,基于毛细补偿浸润与防架桥的缝合结构电池的制备方法包括步骤:将缝合线置于预浸渍液中,经预浸渍处理,得到预浸渍缝合线;将碳纤维结构正极、玻璃纤维隔膜和碳纤维结构负极依次叠放,得到待缝合电池叠层;采用拨开式缝针方式,利用所述预浸渍缝合线对所述待缝合电池叠层进行缝合处理,得到缝合后的电池叠层;将所述缝合后的电池叠层置于涂覆脱模剂的底模上,并依次铺设剥离层、透气毡、导流网、进料管和出料管,经密封胶条和真空袋密封处理,得到待灌注前体;通过所述进料口灌注电解质或电解质前驱液,并利用所述出料管过量排液,得到灌注体;对所述灌注体进行后处理,拆除所述底模、所述剥离层、所述透气毡、所述导流网、所述进料管和所述出料管,得到缝合结构电池。本发明提出“缝合线预浸渍脱气—拨开式低损伤缝合—透气毡压力补偿—导流网刹车区—流体前沿暂停注入—二次真空排液”的组合工艺,实现缝合结构电池的制备;该方法优选利用预浸渍液对缝合线进行预浸渍处理,使缝合线内部微孔被液体预填充,随后采用拨开式缝针方式对干态或半干态的待缝合电池叠层进行低损伤缝合;完成缝合后,利用真空辅助灌注方式导入电解质或电解质前驱液,并使电解质在玻璃纤维隔膜和预浸渍缝合线的毛细作用下自发补偿浸润压实区和线束内部,最后利用所述出料管经二次真空排出多余电解质与残余气泡实现过量排液,再经后处理后拆除底模、剥离层、透气毡、导流网、进料管和出料管,使缝合结构电池兼具较高纤维体积分数、较低阻抗和较好的层间承载能力。同时,利用该方法制得的缝合结构电池,降低缝合过程中对碳纤维电极和玻璃纤维隔膜的切割、刺穿和短路风险,并且减少缝合线束内部空气和缝合压实区干斑,提高电解质浸润均匀性;利用透气毡补偿缝合线迹导致的高度差,降低真空袋架桥和电解质池形成概率;另外,通过利用未被导流网覆盖的区域形成刹车区,实现毛细补偿过程,改善剥离纤维隔膜、缝孔周围和纤维束内部的电解质渗透;且通过过量排液,使得缝合结构电池兼顾电化学性能、能量密度、层间剪切强度和整体模量。
Smart Images

Figure CN122889845A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of structural battery technology, and in particular to a stitched structural battery based on capillary compensation wetting and anti-bridging, and its preparation method. Background Technology
[0002] Existing methods construct a three-dimensional reinforcement network by introducing reinforcing ribs, sutures, or columnar reinforcements along the lamination direction of the structural battery to improve interlayer shear strength and interfacial bonding. The focus of this type of approach is typically on structural reinforcement where the reinforcing ribs penetrate the battery layers or insulating layers. Another method involves creating through-holes in the metal negative electrode of the structural energy storage device, allowing resin or matrix materials to infiltrate through these holes, thereby enhancing the overall load-bearing capacity of the quasi-solid-state capacitor or structural energy storage device. The focus of this type of approach is typically on "negative electrode opening and resin infiltration reinforcement." However, electrochemical and mechanical properties compete with each other in structured batteries. Simply adding reinforcement structures may improve interlayer load-bearing capacity, but it will compress membrane pores and change ion transport paths, leading to reduced capacity utilization or decreased rate performance. When traditional sutures pass through the battery stack, they exert local radial pressure on the glass fiber membrane and carbon fiber electrode, causing the micropores of the glass fiber membrane to flatten and increase tortuosity, which in turn increases charge transfer impedance (Rct) and Weber impedance (Zw), resulting in polarization during high-current discharge. Air is easily trapped in the compacted area around the suture point and inside the wire bundle, making it difficult to completely wet the electrolyte during subsequent filling, forming "dry spots" or loose connection areas that do not contribute to capacity, reducing the utilization rate of active materials. Furthermore, sharp needles or excessive suture tension may directly pierce the glass fiber membrane, cut or damage the carbon fiber electrode, leading to internal micro-short circuits, localized heating, or decreased cycle stability. Meanwhile, during vacuum infusion or vacuum sealing, the stitches can cause local height differences, resulting in bridging around the stitching point of the vacuum bag. This leads to insufficient local compaction and the formation of an "electrolyte pool," which reduces the fiber volume fraction, energy density, and structural modulus.
[0003] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a stitched structure battery based on capillary compensation wetting and anti-bridging and its preparation method, which aims to solve the problems of membrane compaction, wire bundle gas, dry spots, bridging, electrolyte pool and short circuit risk that easily occur in the electrolyte wetting stage after stitching of existing stitched structure batteries.
[0005] The technical solution of the present invention is as follows: A method for fabricating a stitched structure battery based on capillary compensation wetting and anti-bridging includes the following steps: The suture is placed in a pre-impregnation solution and pre-impregnated to obtain a pre-impregnated suture. The carbon fiber positive electrode, glass fiber separator and carbon fiber negative electrode are stacked in sequence to obtain the battery stack to be stitched. Using a split-needle suture method, the pre-impregnated suture thread is used to sew the battery stack to be sutured, resulting in the sutured battery stack. The stitched battery stack is placed on a bottom mold coated with a release agent, and a release layer, a breathable felt, a flow guide net, a feed pipe and a discharge pipe are laid in sequence. After being sealed with sealing strips and a vacuum bag, the precursor to be filled is obtained. Electrolyte or electrolyte precursor solution is injected through the inlet and excess liquid is discharged through the outlet pipe to obtain a filling body; The infusion body is post-processed by removing the bottom mold, the peeling layer, the breathable felt, the guide net, the feed pipe, and the discharge pipe to obtain a stitched structure battery.
[0006] The method for preparing a sutured structure battery based on capillary compensation wetting and anti-bridging, wherein the suture is obtained by twisting multiple strands of fine filaments; Preferably, the suture is selected from one or more of glass fiber thread, aramid thread, quartz fiber thread, Victorinox thread, polyester thread, nylon thread, and surface-insulated fiber thread.
[0007] The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging, wherein the pre-impregnation solution is preferably an electrolyte or electrolyte precursor suitable for zinc-ion structure batteries, including one or more of aqueous zinc salt electrolyte, gel zinc salt electrolyte precursor, and zinc salt electrolyte precursor containing succinic acid.
[0008] The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging, wherein the pre-impregnation treatment time is 1 min-120 min; Preferably, vacuum degassing is performed during the pre-impregnation process; the vacuum degree of the vacuum degassing process is -0.06MPa to -0.1MPa, and the vacuum degassing time is 1min to 30min.
[0009] The method for preparing a suture structure battery based on capillary compensation wetting and anti-bridging, wherein the suture needle used in the open-type suture method includes one of the following: a rounded-end suture needle, a ball-head suture needle, or a suture needle with a rounded tip.
[0010] The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging, wherein the stitches in the stitching process are one or more of the following: parallel stitches, matrix stitches, oblique stitches, locally reinforced stitches, and non-uniform stitches that avoid tabs or active regions. Preferably, the suture tension of the suture process is between 0.1N and 10N.
[0011] The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging is described, wherein the guide net covers 50%-98% of the battery stack area; the distance between the end of the guide net near the discharge pipe and the discharge pipe is 1cm-10cm.
[0012] The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging, wherein the pressure difference between the feed pipe and the discharge pipe is 5 kPa-80 kPa; Preferably, the injection rate of electrolyte or electrolyte precursor solution through the feed inlet is 0.05 mL / min to 10 L / min.
[0013] The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging includes the following steps: after continuous bubble-free liquid appears in the discharge pipe, continue to discharge 5%-50% of the electrolyte or electrolyte precursor liquid relative to the volume of the stitched battery stack; then close the feed pipe and maintain the discharge pipe under vacuum for 10-60 minutes. Preferably, the post-processing includes one of room temperature standing, heat treatment, ultraviolet curing, chemical cross-linking, and encapsulation.
[0014] A stitched structure battery based on capillary compensation wetting and anti-bridging is prepared using the method described above.
[0015] Beneficial Effects: This invention provides a suture-structured battery based on capillary compensation wetting and anti-bridging, and its preparation method. The preparation method of the suture-structured battery based on capillary compensation wetting and anti-bridging includes the following steps: placing suture thread in a pre-impregnation solution for pre-impregnation treatment to obtain pre-impregnated suture thread; sequentially stacking a carbon fiber positive electrode, a glass fiber separator, and a carbon fiber negative electrode to obtain a battery stack to be sutured; and using a split-needle suture method, suturing the battery stack to be sutured with the pre-impregnated suture thread to obtain a sutured battery. The battery stack is then placed on a bottom mold coated with a release agent, and a release layer, a breathable felt, a flow guide net, an inlet pipe, and an outlet pipe are laid in sequence. The stack is then sealed with sealing strips and a vacuum bag to obtain the precursor to be filled. Electrolyte or electrolyte precursor solution is filled through the inlet, and excess liquid is drained through the outlet pipe to obtain the filler body. The filler body is then post-processed by removing the bottom mold, the release layer, the breathable felt, the flow guide net, the inlet pipe, and the outlet pipe to obtain the stitched structure battery. This invention proposes a combined process of "suture pre-impregnation and degassing—open-type low-damage suturing—breathable felt pressure compensation—guide net braking zone—fluid front-end pause injection—secondary vacuum drainage" to achieve the fabrication of suture-structured batteries. This method preferably utilizes a pre-impregnation liquid to pre-fill the suture's internal micropores with liquid. Subsequently, an open-type suture needle is used to perform low-damage suturing of the dry or semi-dry battery stacks. After suturing, electrolyte or electrolyte precursor solution is introduced using vacuum-assisted infusion, allowing the electrolyte to spontaneously compensate for the wetting and compaction zone and the interior of the wire bundle under the capillary action of the glass fiber membrane and pre-impregnated suture. Finally, excess electrolyte and residual air bubbles are discharged through a secondary vacuum via the discharge pipe to achieve excess drainage. After post-processing, the bottom mold, peeling layer, breathable felt, guide net, feed pipe, and discharge pipe are removed, resulting in a suture-structured battery with a high fiber volume fraction, low impedance, and good interlayer load-bearing capacity. Meanwhile, the stitched structure battery prepared using this method reduces the risk of cutting, puncturing, and short-circuiting the carbon fiber electrode and glass fiber separator during the stitching process, and reduces air inside the stitch bundle and dry spots in the stitch compaction zone, improving the uniformity of electrolyte wetting. The use of breathable felt to compensate for the height difference caused by the stitching stitches reduces the probability of vacuum bag bridging and electrolyte cell formation. In addition, by using the area not covered by the guide net to form a braking zone, the capillary compensation process is realized, improving electrolyte permeation around the peeled fiber separator, the pores, and inside the fiber bundle. Furthermore, through excessive liquid drainage, the stitched structure battery achieves a balance of electrochemical performance, energy density, interlaminar shear strength, and overall modulus. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the process flow for a stitched structure battery fabrication method based on capillary compensation wetting and anti-bridging according to the present invention. Figure 2This is a schematic diagram of the structure of the stitched battery stack; Figure 3 This is a schematic diagram of suture pre-impregnation and vacuum degassing. Figure 4 This is a schematic diagram of the vacuum infusion process layout; Figure 5 A schematic diagram of paused injection and capillary compensation infiltration after the electrolyte fluid front reaches the suture zone; Figure 6 This is a schematic diagram of secondary vacuum drainage; Figure 7 The bending stress-strain curves are shown for the unstitched battery structure and the stitched battery structure prepared in Example 1. Figure 8 The graph shows the cycle capacity curves of the unstitched structure battery and the stitched structure battery prepared in Example 1 at a rate of 1.0C. Figure 9 The graph shows the rate performance test data of the unstitched structure battery and the stitched structure battery prepared in Example 1. Figure 10 Metallographic micrograph of the suture needle puncture site; Explanation of reference numerals in the attached drawings: 10 carbon fiber positive electrode, 20 glass fiber diaphragm, 30 carbon fiber negative electrode, 40 stitching, 100 bottom mold, 200 peeling layer, 300 breathable felt, 400 flow guide net, 500 feed pipe, 600 discharge pipe, 700 vacuum bag, 800 flow guide braking zone. Detailed Implementation
[0017] This invention provides a stitched structure battery based on capillary compensation wetting and anti-bridging, and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0018] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as in the context of the prior art, and should not be interpreted in an idealized or overly formal sense unless specifically defined as herein.
[0019] Structural batteries are a type of multifunctional composite material device that combines mechanical load-bearing and electrochemical energy storage functions. Energy storage units are embedded within a carbon fiber composite structure, allowing the structural component to simultaneously bear load and supply energy. Compared to the traditional "structural component + independent battery" design, structural batteries promise to reduce system-level mass, save space, and improve structural integration efficiency, making them suitable for applications such as aerospace, drones, electric vehicles, wearable devices, and lightweight energy storage structures.
[0020] However, structural batteries typically contain materials of different phases, such as carbon fiber reinforcement layers, electrode layers, separators, electrolytes, and resin matrices. Their mechanical load-bearing channels and ion / electron transport channels are coupled together, which can easily lead to problems such as insufficient interfacial bonding, interlayer delamination, uneven electrolyte wetting, local short circuits, and increased electrochemical impedance.
[0021] However, existing solutions focus on "whether to suture" or "whether to implant reinforcing ribs", but lack systematic design for the flow control, capillary compensation, prevention of dry spots, prevention of bridging and secondary drainage process of electrolyte after suturing in batteries.
[0022] Based on this, such as Figure 1 As shown, this invention provides a method for fabricating a stitched structure battery based on capillary compensation wetting and anti-bridging, comprising the following steps: Step S10: Place the suture in the pre-impregnation solution and undergo pre-impregnation treatment to obtain pre-impregnated suture; Step S20: Stack the carbon fiber positive electrode, glass fiber separator and carbon fiber negative electrode in sequence to obtain the battery stack to be stitched; Step S30: Using a split-type suture needle, the pre-impregnated suture thread is used to sew the battery stack to be sewn, resulting in the sewn battery stack; Step S40: Place the stitched battery stack on the bottom mold coated with release agent, and lay the release layer, breathable felt, flow guide net, feed pipe and discharge pipe in sequence. After sealing with sealing strip and vacuum bag, the precursor to be filled is obtained. Step S50: Inject electrolyte or electrolyte precursor solution through the feed inlet and drain excess liquid through the discharge pipe to obtain an injection body; Step S60: Post-process the infusion body by removing the bottom mold, the peeling layer, the breathable felt, the guide net, the feed pipe and the discharge pipe to obtain a stitched structure battery.
[0023] In this embodiment, a combined process of "suture pre-impregnation and degassing—open-type low-damage suturing—breathable felt pressure compensation—guide net braking zone—fluid front-end pause injection—secondary vacuum drainage" is proposed to realize the fabrication of suture structure batteries. The method preferably uses pre-impregnation liquid to pre-fill the suture pores with liquid. Then, open-type suturing needles are used to perform low-damage suturing on the dry or semi-dry battery stacks to be sutured. After suturing, electrolyte or electrolyte precursor liquid is introduced by vacuum-assisted infusion. Under the capillary action of glass fiber membrane and pre-impregnated suture, the electrolyte spontaneously compensates for the wetting and compaction zone and the inside of the wire bundle. Finally, the excess electrolyte and residual air bubbles are discharged through the discharge pipe through secondary vacuum to achieve excess drainage. After post-processing, the bottom mold, peeling layer, breathable felt, guide net, feed pipe and discharge pipe are removed. This makes the suture structure battery have a high fiber volume fraction, low impedance and good interlayer load-bearing capacity. Meanwhile, the stitched structure battery prepared using this method reduces the risk of cutting, puncturing, and short-circuiting the carbon fiber electrode and glass fiber separator during the stitching process, and reduces air inside the stitch bundle and dry spots in the stitch compaction zone, improving the uniformity of electrolyte wetting. The use of breathable felt to compensate for the height difference caused by the stitching stitches reduces the probability of vacuum bag bridging and electrolyte cell formation. In addition, by using the area not covered by the guide net to form a braking zone, the capillary compensation process is realized, improving electrolyte permeation around the peeled fiber separator, the pores, and inside the fiber bundle. Furthermore, through excessive liquid drainage, the stitched structure battery achieves a balance of electrochemical performance, energy density, interlaminar shear strength, and overall modulus.
[0024] Specifically, the method for fabricating a stitched structure battery based on capillary compensation wetting and anti-bridging provided by this invention is applicable to structural battery stacks containing carbon fiber structure electrodes and glass fiber separators; a typical stack may include: a first carbon fiber structure layer, a carbon fiber structure positive electrode layer, a glass fiber separator layer, a carbon fiber structure negative electrode layer, and a second carbon fiber structure layer. The carbon fiber structure positive electrode layer can be a carbon fiber body, carbon fiber with a positive electrode active material loaded on its surface, or carbon fiber coated with a positive electrode conductive paste; the carbon fiber structure negative electrode layer can be a carbon fiber body, metal-deposited carbon fiber, carbon fiber coated with a negative electrode paste, or carbon fiber combined with a metal negative electrode. The positive electrode active layer and / or the negative electrode active layer are preferably arranged towards the glass fiber separator.
[0025] In some embodiments, the structural schematic diagram of the stitched battery stack is as follows: Figure 2 As shown, it includes a carbon fiber positive electrode 10, a glass fiber diaphragm 20 and a carbon fiber negative electrode 30 arranged in sequence, and a suture 40 inserted through the carbon fiber positive electrode 10, the glass fiber diaphragm 20 and the carbon fiber negative electrode 30.
[0026] In some embodiments, the suture is obtained by twisting multiple strands of fine filaments together. The suture obtained by twisting multiple strands of fine filaments allows the multiple strands of fine filaments to slide and disperse bending, stretching, and torsional stresses. When the battery is charged and discharged, the electrode expands / contracts, the module vibrates, and the assembly is squeezed, resulting in slight displacement. The twisted suture can buffer the deformation stress and will not bend or break like a single thick filament, thus greatly improving the cycle life. In addition, the overall tensile strength is higher and the wear resistance is better, while the suture is less likely to break.
[0027] In some embodiments, the stitching thread is selected from, but is not limited to, one or more of glass fiber threads, aramid threads, quartz fiber threads, Vectran threads, polyester threads, nylon threads, and surface-insulated fiber threads. Pre-impregnating the stitching thread in a pre-impregnation solution removes air from the wire bundle, making the stitching thread a microscale capillary fluid-conducting channel, reducing poor connections, dry spots, and localized impedance increases. Simultaneously, the stitching thread possesses high tensile strength and flexibility, improving the overall strength of the stitched structure battery.
[0028] In some embodiments, the pre-impregnation solution is preferably an electrolyte or electrolyte precursor suitable for zinc-ion structure batteries, including one or more of aqueous zinc salt electrolytes, gel zinc salt electrolyte precursors, and zinc salt electrolyte precursors containing succinic acid.
[0029] In some embodiments, the aqueous zinc salt electrolyte can be one or more of the following: zinc sulfate aqueous solution, zinc trifluoromethanesulfonate aqueous solution, zinc acetate aqueous solution, zinc chloride aqueous solution, and zinc perchlorate aqueous solution. The gel zinc salt electrolyte precursor can be one or more of the following: a precursor containing zinc salt and polyvinyl alcohol, polyethylene oxide, polyacrylamide, polyacrylic acid, gelatin, polyvinylidene fluoride-hexafluoropropylene, or other gel matrix. The zinc salt electrolyte precursor containing succinate can be one or more of the following: a mixture of succinate and zinc salt, plasticizer, carbonate solvent, ionic liquid, or polymer monomer.
[0030] In other embodiments, the pre-impregnation solution may also be selected from one or more of the following, depending on the type of structural energy storage device: lithium-ion, sodium-ion, magnesium-ion, aluminum-ion, or supercapacitor system electrolyte precursor solution, gel electrolyte precursor solution, ionic liquid, carbonate solvent, and polymer monomer solution.
[0031] Pre-impregnating the suture with the above-mentioned pre-impregnation solution can remove air from the suture bundle, making the suture a micro-scale capillary fluid channel, reducing poor connections, dry spots, and localized impedance increases.
[0032] In some embodiments, the pre-impregnation treatment time is 1 min to 120 min; within this pre-impregnation treatment time, the pre-impregnation liquid can completely wet the suture, making the suture a microscale capillary fluid channel, reducing loose connections, dry spots and local impedance increases.
[0033] In a preferred embodiment, the pre-impregnation treatment time is 5 min to 60 min.
[0034] In some embodiments, a schematic diagram of suture pre-impregnation and vacuum degassing is shown below. Figure 3 As shown, vacuum degassing is performed during the pre-impregnation process; the vacuum degree of the vacuum degassing process is -0.06MPa to -0.1MPa, and the vacuum degassing time is 1min to 30min. Vacuum degassing allows the pre-impregnation liquid to enter the capillary channels inside the multi-strand suture, improving the air removal effect inside the suture bundle, making the suture a microscale capillary fluid-conducting channel, and reducing loose connections, dry spots, and localized impedance increases.
[0035] In a preferred embodiment, the vacuum degree of the vacuum degassing treatment is -0.1 MPa, and the vacuum degassing treatment time is 15 min.
[0036] In some embodiments, the pre-impregnation treatment further includes: removing excess liquid from the surface of the suture, so that the pre-impregnation liquid remains in the micropores inside the suture bundle.
[0037] In some embodiments, in step S20, the battery stack to be stitched is preferably a dry stack or a semi-dry stack, that is, no large amount of liquid electrolyte is injected before stitching, so as to reduce the risk of electrolyte leakage, diaphragm puncture and internal short circuit during the stitching process.
[0038] In some embodiments, the needles used in the prying-opening suture method include, but are not limited to, rounded-end needles, ball-tipped needles, and needles with rounded tips. The needle tips of these needles do not have sharp cutting edges. Using low-damage fiber-prying sutures to sew the battery stack allows the needle to pry open the carbon fiber bundles and glass fiber separator fibers during sewing, rather than cutting the fibers. By using needles of this shape to achieve penetration by prying open the fiber bundles rather than cutting the fibers, the probability of carbon fiber electrode damage, puncture of the fiber separator, and micro-short circuits is reduced.
[0039] In some embodiments, the suture stitches used in the suturing process are, but are not limited to, one or more of the following: parallel stitches, matrix stitches, oblique stitches, locally reinforced stitches, and non-uniform stitches that avoid the tabs or active areas. Different suture stitches or combinations of multiple suture stitches can be selected according to actual needs to achieve the suturing process of the battery stack to be sutured.
[0040] In some embodiments, the suture density of the suture treatment is (3-10) mm × (3-10) mm. For example, it can be, but is not limited to: 10 mm × 10 mm (low density), 5 mm × 5 mm (medium density), and 3 mm × 3 mm (high density) to adapt to the balance requirements of different mechanical enhancements in electrochemical performance.
[0041] In some embodiments, the suture tension of the suture process is between 0.1N and 10N; controlling the suture tension of the suture process between 0.1N and 10N can ensure positioning and reinforcement effects while reducing fiber damage.
[0042] In some embodiments, the vacuum infusion process layout diagram in step S40 is as follows: Figure 4 As shown, the stitched battery stack is placed on a bottom mold 100 coated with a release agent, and a release layer 200, a breathable felt 300, a flow guide net 400, a feed pipe 500, and a discharge pipe 600 are sequentially laid on the stitched battery stack. After being sealed with a sealing strip and a vacuum bag 700, the precursor to be injected is obtained; wherein, the end of the flow guide net near the discharge pipe forms a flow guide braking zone 800 with the discharge pipe.
[0043] In some embodiments, in step S40, the breathable felt is preferably a peelable process auxiliary layer located between the peeling layer and the flow guide net. It compensates for local height differences caused by sutures during the filling and pressure holding stages. After curing or gelling, it is removed with the peeling layer and is not a necessary component of the final sewn-structure battery. Specifically, the breathable felt is used to achieve pressure compensation, filling the height differences caused by sutures like a compressible buffer layer, ensuring uniform pressure transmission in the vacuum bag, and preventing bridging and electrolyte pooling.
[0044] In some embodiments, the breathable felt is selected from, but not limited to, compressible nonwoven fabric, polyester felt, fiberglass felt, bubble wrap, peelable porous membrane, or other compressible process auxiliary layers.
[0045] In some embodiments, the guide net covers 50%-98% of the battery stack area; the distance between the end of the guide net near the discharge pipe and the discharge pipe is 1cm-10cm. By controlling the coverage area of the guide net on the battery stack and controlling the distance between the end of the guide net near the discharge pipe and the discharge pipe, a flow-guiding braking zone can be formed. This zone (the area not covered by the guide net) reduces the velocity of the electrolyte fluid front, prolongs the residence time of the electrolyte inside the battery, slows down the electrolyte fluid inside the battery and provides lateral compensation wetting, promoting full wetting of the glass fiber separator and the seam compaction zone.
[0046] In some implementations, the flow-guiding braking zone can be achieved by shortening the flow-guiding net, reducing the flow-guiding net permeability, setting local flow-blocking strips, using zoned flow-guiding nets, or using multi-level flow-guiding nets.
[0047] In a preferred embodiment, the flow guide net covers 70%-95% of the battery stack area; the distance between the end of the flow guide net near the discharge pipe and the discharge pipe is 3cm-5cm. This creates a flow guide net braking zone in the area not covered by the flow guide net, reducing the electrolyte flow rate and preventing the electrolyte from rapidly bypassing along a high-permeability path, thus forcing it to remain and permeate within the battery stack.
[0048] In some embodiments, in step S50, electrolyte or electrolyte precursor solution is injected through the feed port under vacuum-assisted conditions, and the pressure difference between the feed pipe and the discharge pipe is 5 kPa-80 kPa, preferably 10 kPa-50 kPa; the injection rate of electrolyte or electrolyte precursor solution through the feed port is 0.05 mL / min-10 L / min, preferably 0.1 mL / min-5 L / min.
[0049] Specifically, the schematic diagram of the pause in injection and capillary compensation infiltration after the electrolyte fluid front reaches the suture zone is shown below. Figure 5 As shown, when the leading edge of the electrolyte or electrolyte precursor solution reaches the suture array area or dense suture area, the injection of the electrolyte or electrolyte precursor solution is paused for 1-10 minutes, allowing the electrolyte or electrolyte precursor solution to spontaneously enter the area around the suture opening, the compaction zone, and the interior of the suture bundle through capillary action between the pre-impregnated sutures, the glass fiber diaphragm, and the carbon fiber bundle. Preferably, the injection of the electrolyte or electrolyte precursor solution is paused for 2-5 minutes, utilizing the capillary suction of the sutures and the glass fiber diaphragm to compensate for insufficient microscopic wetting in the suture compaction zone.
[0050] In some implementations, the injection pause can be controlled based on the fluid front position, the state of the bubbles at the outlet, changes in pressure difference, changes in conductivity, or visual observation signals.
[0051] In this embodiment, the electrolyte permeation of the glass fiber diaphragm, around the pores, and inside the fiber bundle can be improved through the flow guide network braking zone and the capillary compensation process of paused injection.
[0052] In some embodiments, the step of excessively draining liquid using the discharge pipe includes: after continuous bubble-free liquid appears in the discharge pipe, continuing to discharge 5%-50% of the electrolyte or electrolyte precursor liquid relative to the volume of the stitched battery stack; then closing the feed pipe and maintaining the discharge pipe under vacuum for 10-60 minutes.
[0053] In a preferred embodiment, a schematic diagram of secondary vacuum drainage is shown below. Figure 6As shown, after a continuous flow of bubble-free liquid appears in the discharge pipe, 10%-30% of the electrolyte or electrolyte precursor solution relative to the volume of the stitched battery stack continues to be discharged; then the feed pipe is closed, and the discharge pipe is kept under vacuum for 15-30 minutes to perform secondary vacuum drainage and degassing treatment to remove residual bubbles and excess electrolyte, reduce the electrolyte pool, improve the fiber volume fraction and interlayer compaction uniformity, and reduce the decrease in modulus and energy density caused by excess electrolyte.
[0054] In some implementations, the secondary vacuum can be replaced or combined with pulsed vacuum, stepped pressure reduction, periodic opening and closing of the feed valve, alternating positive and negative pressure, or centrifugal-assisted drainage.
[0055] In some embodiments, the post-processing includes one of room temperature standing, heat treatment, ultraviolet curing, chemical crosslinking, and encapsulation. Depending on the properties of the electrolyte or electrolyte precursor solution, room temperature standing, heat treatment, ultraviolet curing, chemical crosslinking, or encapsulation are performed to form a stable liquid, gel, quasi-solid, or resin-based electrolyte state, resulting in a low-damage stitched structure battery.
[0056] In some embodiments, the stitched structure battery can be a zinc-ion battery, a lithium-ion battery, a sodium-ion battery, a magnesium-ion battery, an aluminum-ion battery, an aqueous battery, a gel electrolyte battery, or a resin-based electrolyte structure battery.
[0057] In addition, the present invention also provides a stitched structure battery based on capillary compensation wetting and anti-bridging, which is prepared by the method of the stitched structure battery based on capillary compensation wetting and anti-bridging.
[0058] In this embodiment, the stitched structure battery prepared by this method reduces the risk of cutting, puncturing, and short-circuiting the carbon fiber electrode and glass fiber separator during the stitching process, and reduces air inside the stitch bundle and dry spots in the stitch compaction area, improving the uniformity of electrolyte wetting. The breathable felt is used to compensate for the height difference caused by the stitching, reducing the probability of vacuum bag bridging and electrolyte cell formation. In addition, by using the area not covered by the guide net to form a braking zone, the capillary compensation process is realized, improving electrolyte permeation around the peeled fiber separator, the pores, and inside the fiber bundle. Furthermore, through excessive liquid drainage, the stitched structure battery achieves a balance of electrochemical performance, energy density, interlaminar shear strength, and overall modulus.
[0059] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention.
[0060] Example 1 This embodiment provides a stitched structure battery based on capillary compensation wetting and anti-bridging, and its preparation method is as follows: Glass fiber sutures with a suture density of 10 mm × 10 mm were used. The sutures were pre-impregnated with an electrolyte precursor solution containing succinic anhydride (SN) for 30 min and then degassed under vacuum at a vacuum degree of -0.1 MPa. A blunt-end suture was used to perform low-damage suturing of the carbon fiber positive electrode / glass fiber separator / carbon fiber negative electrode stack. Then, the electrolyte was introduced according to the vacuum-assisted infusion method of this invention. After the fluid front reached the suture area, it was paused for about 3 min. After continuous bubble-free liquid appeared at the discharge end, about 20% of the cell volume of electrolyte was discharged and a second vacuum treatment was performed for about 20 min. After standing at room temperature, the bottom mold, peeling layer, breathable felt, guide net, feed pipe and discharge pipe were removed to obtain the sutured structure battery.
[0061] Example 2 This embodiment is largely the same as Embodiment 1, except for the different suture density.
[0062] Except for the stitching density being set to 10 mm × 10 mm, 5 mm × 5 mm, and 3 mm × 3 mm, the remaining steps were the same as in Example 1. This example was used to compare the interlayer load-bearing capacity, electrolyte wetting uniformity, and electrochemical impedance changes of the structural battery under low-density, medium-density, and high-density stitching conditions, thereby determining the balance range between mechanical and electrochemical performance.
[0063] Example 3 This embodiment is largely the same as Embodiment 1, except for the different capillary pause times.
[0064] Except for the pause times after the electrolyte fluid front reaches the suture zone, which are set to 2 min, 5 min, and 10 min respectively, the remaining steps are the same as in Example 1. This example is used to verify the effect of the pause injection time on the wetting effect inside the suture bundle, around the suture opening, and in the compacted area of the glass fiber diaphragm.
[0065] Example 4 This embodiment is largely the same as Embodiment 1, except that the type of pre-impregnation solution is different.
[0066] Specifically, the pre-impregnation solutions adopt the following systems: The first group uses an aqueous zinc salt electrolyte, wherein the aqueous zinc salt electrolyte is an aqueous solution of zinc sulfate, an aqueous solution of zinc trifluoromethanesulfonate, an aqueous solution of zinc acetate, an aqueous solution of zinc chloride, or a combination thereof; The second group uses a gel zinc salt electrolyte precursor solution, which includes a zinc salt, a gel matrix, and a solvent. The gel matrix can be polyvinyl alcohol, polyethylene oxide, polyacrylamide, polyacrylic acid, gelatin, or polyvinylidene fluoride-hexafluoropropylene. The third group uses a zinc salt electrolyte precursor solution containing succinic acid, wherein the zinc salt electrolyte precursor solution containing succinic acid includes succinic acid, zinc salt and plasticizer or solvent; The fourth group uses a polymer monomer precursor solution for aqueous or quasi-solid-state zinc-ion structure batteries. The polymer monomer precursor solution includes acrylamide, acrylic acid, methyl methacrylate, polyethylene glycol diacrylate or a combination thereof, and contains zinc salt.
[0067] Except for the type of pre-impregnation solution, the remaining steps are the same as in Example 1. This example illustrates that different zinc-ion electrolytes or zinc-ion electrolyte precursor solutions can improve the electrolyte wetting effect of subsequent zinc-ion batteries by pre-filling the capillary channels inside the suture and expelling air from the wire bundle.
[0068] Comparative Example 1: The sutures were not pre-impregnated or degassed; the remaining steps were the same as in Example 1. This comparative example was used to verify the effect of suture pre-impregnation and degassed treatment on reducing air bubbles, loose joints, and dry spots within the suture bundle.
[0069] Comparative Example 2: No breathable felt was used; the remaining steps were the same as in Example 1. This comparative example was used to verify the effect of the breathable felt as a pressure compensation layer on reducing vacuum bag bridging, localized insufficient compaction, and the formation of electrolyte pools.
[0070] Comparative Example 3: No pause was made during electrolyte perfusion; the remaining steps were the same as in Example 1. This comparative example was used to verify the effect of capillary compensation pause based on the fluid front position on reducing local impedance in the suture area and improving the uniformity of diaphragm wetting.
[0071] Comparative Example 4: Ordinary pointed needle suturing was used, with the remaining steps identical to Example 1. This comparative example was used to verify the effect of round-tipped or blunt-tipped needle fiber-removing suturing on reducing the risk of carbon fiber electrode damage, diaphragm puncture, and internal micro-short circuits.
[0072] Comparative Example 5: No secondary vacuum treatment was performed; all other steps were the same as in Example 1. This comparative example was used to verify the effect of secondary vacuum drainage and venting on reducing residual bubbles, lowering the electrolyte level, and maintaining a high fiber volume fraction.
[0073] To further illustrate the verifiability of the technical solution of this invention, the structural batteries prepared in Examples 1-4 and Comparative Examples 1-5 can be evaluated for performance as follows. The following test items are used to characterize the technical effects of this invention in improving electrolyte wetting, reducing suture damage, reducing dry spots and bubbles, suppressing vacuum bag bridging, and maintaining the overall mechanical-electrochemical performance of the structural battery, and do not limit this invention to the requirement that all test items be performed simultaneously.
[0074] Optional (including those already tested) test items: 1. Electrochemical impedance spectroscopy (EIS), including Rct and Zw, is used to evaluate whether capillary compensation wetting helps reduce interfacial charge transfer impedance and diffusion impedance, especially to determine whether effective ion transport can still be maintained after compaction of the suture zone.
[0075] 2. Short beam shear test or interlaminar shear strength test is used to evaluate whether the stitching treatment and anti-bridging treatment help improve the interlaminar load-bearing capacity of the structural cell.
[0076] 3. Three-point bending test is used to evaluate the overall bending strength, bending modulus and failure mode changes of the structural battery.
[0077] Three-point bending tests were performed on the unstitched battery structure and the stitched battery structure prepared in Example 1. The bending stress-strain curves are shown in the figure. Figure 7 As shown, the stitched structure battery exhibits a larger bending strain under the same bending stress.
[0078] 4. Cyclic performance and capacity retention tests are used to evaluate whether low-damage suturing and post-impregnation processes can maintain electrochemical stability while enhancing structural performance.
[0079] Cycle performance and capacity retention were tested on the unstitched battery structure and the stitched battery structure prepared in Example 1. The cycle capacity curves of the unstitched battery structure at 1.0C rate are shown in the figure. Figure 8 As shown.
[0080] 5. Rate performance test, used to evaluate whether improved wetting uniformity can reduce polarization and improve discharge capability under higher current conditions.
[0081] Rate performance tests were conducted on the unstitched battery structure and the stitched battery structure prepared in Example 1. The rate performance test data are shown in the figure below. Figure 9 As shown.
[0082] 6. Metallographic microscopy at the needle puncture site is used to observe whether there is fiber damage near the carbon fiber structure electrode in the suture area.
[0083] Metallographic micrograph of the suture needle puncture site as shown in the image. Figure 10As shown, the left image is a sutured perforation without impregnation, and obvious fiber damage can be observed at the perforation site; the right image is a sutured perforation after impregnation, and no obvious fiber damage is observed.
[0084] In summary, this invention provides a suture-structured battery based on capillary compensation wetting and anti-bridging, and its preparation method. The preparation method of the suture-structured battery based on capillary compensation wetting and anti-bridging includes the following steps: placing suture thread in a pre-impregnation solution for pre-impregnation treatment to obtain pre-impregnated suture thread; sequentially stacking a carbon fiber positive electrode, a glass fiber separator, and a carbon fiber negative electrode to obtain a battery stack to be sutured; and using a split-type suture needle, suturing the battery stack to be sutured with the pre-impregnated suture thread to obtain a suture-structured battery. The assembled battery stack is placed on a bottom mold coated with a release agent, and a release layer, a breathable felt, a flow guide net, an inlet pipe, and an outlet pipe are laid in sequence. After sealing with sealing strips and a vacuum bag, a precursor to be filled is obtained. Electrolyte or electrolyte precursor solution is filled through the inlet, and excess liquid is drained through the outlet pipe to obtain a filler body. The filler body is post-processed by removing the bottom mold, the release layer, the breathable felt, the flow guide net, the inlet pipe, and the outlet pipe to obtain a stitched structure battery. This invention proposes a combined process of "suture pre-impregnation and degassing—open-type low-damage suturing—breathable felt pressure compensation—guide net braking zone—fluid front-end pause injection—secondary vacuum drainage" to achieve the fabrication of suture-structured batteries. This method preferably utilizes a pre-impregnation liquid to pre-fill the suture's internal micropores with liquid. Subsequently, an open-type suture needle is used to perform low-damage suturing of the dry or semi-dry battery stacks. After suturing, electrolyte or electrolyte precursor solution is introduced using vacuum-assisted infusion, allowing the electrolyte to spontaneously compensate for the wetting and compaction zone and the interior of the wire bundle under the capillary action of the glass fiber membrane and pre-impregnated suture. Finally, excess electrolyte and residual air bubbles are discharged through a secondary vacuum via the discharge pipe to achieve excess drainage. After post-processing, the bottom mold, peeling layer, breathable felt, guide net, feed pipe, and discharge pipe are removed, resulting in a suture-structured battery with a high fiber volume fraction, low impedance, and good interlayer load-bearing capacity. Meanwhile, the stitched structure battery prepared using this method reduces the risk of cutting, puncturing, and short-circuiting the carbon fiber electrode and glass fiber separator during the stitching process, and reduces air inside the stitch bundle and dry spots in the stitch compaction zone, improving the uniformity of electrolyte wetting. The use of breathable felt to compensate for the height difference caused by the stitching stitches reduces the probability of vacuum bag bridging and electrolyte cell formation. In addition, by using the area not covered by the guide net to form a braking zone, the capillary compensation process is realized, improving electrolyte permeation around the peeled fiber separator, the pores, and inside the fiber bundle. Furthermore, through excessive liquid drainage, the stitched structure battery achieves a balance of electrochemical performance, energy density, interlaminar shear strength, and overall modulus.
[0085] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.
Claims
1. A method for fabricating a stitched structure battery based on capillary compensation wetting and anti-bridging, characterized in that, Including the following steps: The suture is placed in a pre-impregnation solution and pre-impregnated to obtain a pre-impregnated suture. The carbon fiber positive electrode, glass fiber separator and carbon fiber negative electrode are stacked in sequence to obtain the battery stack to be stitched. Using a split-needle suture method, the pre-impregnated suture thread is used to sew the battery stack to be sutured, resulting in the sutured battery stack. The stitched battery stack is placed on a bottom mold coated with a release agent, and a release layer, a breathable felt, a flow guide net, a feed pipe and a discharge pipe are laid in sequence. After being sealed with sealing strips and a vacuum bag, the precursor to be filled is obtained. Electrolyte or electrolyte precursor solution is injected through the inlet and excess liquid is discharged through the outlet pipe to obtain a filling body; The infusion body is post-processed by removing the bottom mold, the peeling layer, the breathable felt, the guide net, the feed pipe, and the discharge pipe to obtain a stitched structure battery.
2. The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging according to claim 1, characterized in that, The suture is made of multiple strands of fine filament twisted together; Preferably, the suture is selected from one or more of glass fiber thread, aramid thread, quartz fiber thread, Victorinox thread, polyester thread, nylon thread, and surface-insulated fiber thread.
3. The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging according to claim 1, characterized in that, The pre-impregnation solution is an electrolyte or electrolyte precursor suitable for zinc-ion structure batteries, including one or more of aqueous zinc salt electrolytes, gel zinc salt electrolyte precursors, and zinc salt electrolyte precursors containing succinic acid.
4. The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging according to claim 1, characterized in that, The pre-impregnation treatment time is 1 min to 120 min; Preferably, vacuum degassing is performed during the pre-impregnation process; the vacuum degree of the vacuum degassing process is -0.06MPa to -0.1MPa, and the vacuum degassing time is 1min to 30min.
5. The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging according to claim 1, characterized in that, The needles used in the split-type suturing method include one of the following: blunt-ended needles, ball-head needles, and needles with rounded tips.
6. The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging according to claim 1, characterized in that, The suture stitches used in the suturing process are one or more of the following: parallel stitches, matrix stitches, oblique stitches, locally reinforced stitches, and non-uniform stitches that avoid the tabs or active areas. Preferably, the suture tension of the suture process is between 0.1N and 10N.
7. The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging according to claim 1, characterized in that, The flow guide net covers 50%-98% of the battery stack area; the distance between the end of the flow guide net closest to the discharge pipe and the discharge pipe is 1cm-10cm.
8. The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging according to claim 1, characterized in that, The pressure difference between the feed pipe and the discharge pipe is 5 kPa-80 kPa; Preferably, the injection rate of electrolyte or electrolyte precursor solution through the feed inlet is 0.05 mL / min to 10 L / min.
9. The method for preparing a stitched structure battery based on capillary compensation wetting and anti-bridging according to claim 1, characterized in that, The step of excessively draining liquid using the discharge pipe includes: after continuous bubble-free liquid appears in the discharge pipe, continuing to discharge 5%-50% of the electrolyte or electrolyte precursor liquid relative to the volume of the stitched battery stack; then closing the feed pipe and maintaining the discharge pipe under vacuum for 10-60 minutes; Preferably, the post-processing includes one of room temperature standing, heat treatment, ultraviolet curing, chemical cross-linking, and encapsulation.
10. A stitched structure battery based on capillary compensation wetting and anti-bridging, characterized in that, The battery was prepared using the method described in claims 1-9 for fabricating a stitched structure battery based on capillary compensation wetting and anti-bridging.